Volatile sulphur compounds in wines related to yeast metabolism and nitrogen composition of grape musts - Moreira, N. (2011)
The influence of nitrogen compounds in grape musts on the content of sulphur compounds of wines was studied. Different vinifications were performed with the addition of methionine (20 mg l−1) and/or cysteine (40 mg l−1) to grape musts before alcoholic fermentation. Six grape musts, with different nitrogen composition, from cultivars of the ‘Vinhos Verdes’ Region, in Portugal, were used. Addition of methionine to grape musts enhanced the content of wines in 3-(methylthio)-1-propanol, acetic acid-3-(methylthio)propyl ester, 3-(methylthio)propionic acid and some unidentified sulphur compounds. Increase of cysteine concentration in musts led to the production of wines with high levels of hydrogen sulphide and cis-2-methyltetrahydrothiophene- 3-OL and also unidentified sulphur compounds; however, the content of 3-(methylthio)propionic acid in the wines decreased considerately with the addition of cysteine to grape musts. This work showed that cultivars from the Vinho Verde Region show different sulphur compound contents. Avesso wines, elaborated from grape musts with low amino acids level, presented the highest total sulphur compounds content. Wines from Azal branco and Alvarinho were characterised by high contents of 4-(methylthio)-1-butanol and 3-(methylthio)propionic acid, respectively. A high content of N-(3-(methylthio) propyl)-acetamide and dimethylsulphone characterise the Loureiro wines. In contrast, Trajadura wines, produced from a must rich in amino acids, presented a low total sulphur compounds content; however, these wines were also characterised by high concentrations of 4-(methylthio)-1-butanol, acetic acid-3-(methylthio)propyl ester and hydrogen sulphide.